Pelatihan Pengemasan, Pelabelan dan Digital Marketing Produk Black Garlic di Kota Payakumbuh Sumatera Barat - Nesti, Lisa; Meilizar; Jamsan, Firdaus; Musdirwan; Elviana, Rahmi; Sutri, Reni (Journal of Industrial Community Empowerment, 2023)
Payakumbuh City, is one of the centres of garlic production in West Sumatra. In the city, an industry has been established for the manufacture and marketing of health products, one of them is fermented garlic (black garlic). The lack of knowledge, technology, attention from the government and related parties is an obstacle for the community to develop this business. After this community service activity, it is hoped that they can improve and develop their black garlic product through packaging, labelling and digital marketing. The method of implementing this activity is done by providing material and demonstration of packaging, labelling and digital marketing of black garlic products. This activity was accompanied by instructors (lecturers) and continued with practice by participants. The output that has been achieved is that the community understands the technology of packaging and labelling of black garlic products which have added value in order to compete widely.